Perubahan Patologi Anatomi Hati dan Saluran Empedu Sapi Aceh Yang Terinfeksi Fasciola gigantica - Ummu Balqis; Darmawi Darmawi; Siti Aisyah; Muhammad Hambal (Agricultural Faculty, 2013)
Pathology anatomy changes in liver and bile duct of Aceh cattle infected with fasciola giganticABSTRACT. This study was conducted in Banda Aceh Municipality, Aceh Province to report the pathological changes in liver of Aceh cattle infected with Fasciola gigantica. In this study, livers of male aceh cattles were collected from slaughter area when Qurban in Idul Adha during two years (2011 to 2012). A total of 15 aceh cattle livers were examined. Establishment of F. gigantica were observed, and pathological changes of liver were identified. The result showed that out of 15 male Aceh cattle livers 6 (40%) were found infected with F. gigantica. The common pathological changes found in this study were the hepatic damage, and the bile ducts were changes in size and shape with the dilated lumen. The bile ducts were found filled with blackish brown exudate, which contained adult F. gigantica. In conclusion, fascioliasis is greatly responsible for hepatic damage, and currently expanding as an important veterinary public health problem.